Chronic disease management programme in people with severe knee osteoarthritis: efficacy and moderators of response. - Lamb, S; Toye, F; Barker, K (2008)
AIMS: To establish (1) the efficacy of a six-week chronic disease management programme for knee osteoarthritis and (2) whether previous physiotherapy or being wait listed for surgery moderated the outcome of the programme. DESIGN: A pretest, posttest design with multivariate statistical modelling. PARTICIPANTS: One hundred and twenty-one people with severe osteoarthritis who were waiting, or being considered, for surgery. METHODS AND MEASURES: Western Ontario Osteoarthritis Index (WOMAC) scores, arthritis self-efficacy, distress and a patient-rated global indicator of response were collected at baseline, 6 and 12 weeks. History of previous physiotherapy, waiting list status, symptom duration, New Zealand disease severity score, radiographic changes and self-perceived need for surgery were recorded at baseline. RESULTS: There were moderate improvements in most outcomes; WOMAC function decreased by 0.29, WOMAC pain by 0.27, pain self-efficacy by 4.4, function self-efficacy by 5.6 and visual analogue scale (VAS) distress by 0.2 (effect sizes ranging from 0.3 to 0.5 at 12 weeks). Waiting list status was a significant modifier for function, pain, distress and self-related outcomes. Participants on the waiting list for surgery experienced lesser improvements. Previous physiotherapy was associated with greater improvements in WOMAC scores at six weeks, but not at 12 weeks. CONCLUSION: The chronic disease management programme could be considered for people with severe knee osteoarthritis, but should be given prior to referral and placement on the waiting list for surgery. Previous physiotherapy should not preclude people from participating in a chronic disease management programme.